Sinterização, caracterização e propriedades de compósitos vidro-minerais para uso como revestimentos - Santos, Gisele Guimarães dos (2017)
Engineered stones, commonly known in Brazil as quartz surfaces, are materials used as large tiles for application in architecture and interior decoration. These materials consist of about 90% by weight of mineral particles of various shapes (usually quartz, but mica and feldspar are also used) dispersed in a polymer resin matrix. Despite its aesthetic appeal, the use of a polymer matrix leads to low wear resistance, low chemical resistance and great possibility of degradation of the polymer by UV rays and permanent marks by contact with hot objects. Thus, this project objective was the development and optimization of compositions and conditions of thermal treatment, characterization and viability of engineered stones with glass instead of a polymer matrix. Glass-mineral composites containing up to 70% weight of albite, alumina, petalilte and quartz (the rest being recycled window glass) were studied, with special attention in obtaining samples with low porosity. The composites were also characterized in relation to some properties, such as flexural strength, hardness, Kc, water absorption, resistance to thermal shock and resistance to chemical attack. With the exception of Quartz / Glass composites, it was possible to obtain materials of low porosity and diverse competitive properties in relation to other products already available. A composition containing glass and alumina had a flexural strength of 115 MPa and a hardness of 9 GPa; The composite of petalite and glass exhibited greater resistance to thermal shock; The albite and glass composite exhibited better resistance to chemical attack practically unchanged even when in contact with solutions of NaOH 10% (v / v), acetic acid 10% (v / v) and citric acid 3 g / L.